1987
DOI: 10.1523/jneurosci.07-04-01031.1987
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of reinnervation of rat internal intercostal muscles by their own segmental nerves

Abstract: The positions of internal intercostal motoneurons within their motor pool were studied, following reinnervation of the intercostal muscles by their original nerves. Six to 9 weeks after proximal nerve section in 10-d-old and adult rats, 0.1 microliter injections of wheat germ agglutinin (WGA)-HRP were made in the distal part of the reinnervated internal intercostal muscle. The corresponding region of the contralateral control muscle was also injected. The positions of the retrogradely labeled motoneurons were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…It is very clear that skeletal muscle is not a homogeneous tissue from the viewpoint of developing or regenerating motoneurones. For instance, motoneurones are evidently capable of making crude distinction between muscles on the basis of their position or segmental origin (Bennett & Lavidis, 1984;Wigston & Sanes, 1985;Donahue & English, 1987, 1989Hardman & Brown, 1987;Balice-Gordon & Thompson, 1988;Bennett & Ho, 1988;Laskowski & Sanes, 1988;Laskowski & High, 1989). Other data suggest that matching of motor terminals to muscle fibres of a pre-specified, complementary type is important in competition, both during postnatal development and following reinnervation in adults.…”
Section: Role Of Selective Synapse Formation and Eliminationmentioning
confidence: 99%
“…It is very clear that skeletal muscle is not a homogeneous tissue from the viewpoint of developing or regenerating motoneurones. For instance, motoneurones are evidently capable of making crude distinction between muscles on the basis of their position or segmental origin (Bennett & Lavidis, 1984;Wigston & Sanes, 1985;Donahue & English, 1987, 1989Hardman & Brown, 1987;Balice-Gordon & Thompson, 1988;Bennett & Ho, 1988;Laskowski & Sanes, 1988;Laskowski & High, 1989). Other data suggest that matching of motor terminals to muscle fibres of a pre-specified, complementary type is important in competition, both during postnatal development and following reinnervation in adults.…”
Section: Role Of Selective Synapse Formation and Eliminationmentioning
confidence: 99%
“…Progressive differential gene expression would support the production of expanding neural networks congruent with the initial stabilization of segments of dendritic outgrowth and spine formation. Diffusible factors (soluble chemoattractant molecules in the extracellular matrix) released from target neurons are thought to play an important role in facilitating both the distal guidance and proximal homing of axonal outgrowth to specific neurons (Tessier-Lavigne, Placzek, Lumsden, Dodd, & Jessell, 1988) and perhaps axonal homing to specific dendritic areas (e.g., Hardman & Brown, 1987;Yamamoto, Kurotani, & Toyama, 1989). Along with these chemoattractants, the formation of plasma membrane oligosaccharides and carbohydrate-binding proteins would promote protein-protein and protein-carbohydrate interactions that facilitate cell recognition and adhesion (Hynes, Dodd, & Jessell, 1989;Schlosshauer, 1985).…”
Section: Developmental Buffering Of Antisnake Behaviormentioning
confidence: 99%
“…Selective reinnervation has been reported to occur after transection of motor axons in neonatal rats, 2,14 larval anurans, 10 and adult urodeles. 29 Hardman and Brown 14 demonstrated that reinnervation of intercostal muscles of neonatal rats was topographically correct, whereas reinnervation in adult rats appeared to be random. Further, Gillespie et al 12 demonstrated nonselective innervation of rat lateral gastrocnemius and soleus muscles when the common nerve branch to these muscles was cut and sutured to the lateral gastrocnemius muscle.…”
mentioning
confidence: 99%